2013
DOI: 10.1378/chest.12-1788
|View full text |Cite
|
Sign up to set email alerts
|

Response of Chronic Cough to Acid-Suppressive Therapy in Patients With Gastroesophageal Reflux Disease

Abstract: Background: Epidemiologic and physiologic studies suggest an association between gastroesophageal refl ux disease (GERD) and chronic cough. However, the benefi t of antirefl ux therapy for chronic cough remains unclear, with most relevant trials reporting negative fi ndings. This systematic review aimed to reevaluate the response of chronic cough to antirefl ux therapy in trials that allowed us to distinguish patients with or without objective evidence of GERD. Methods: PubMed and Embase systematic searches id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
105
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(117 citation statements)
references
References 40 publications
5
105
0
7
Order By: Relevance
“…In our series, 88 of 156 patients reported an unsatisfactory response to PPIs, which is in agreement with findings of a recent meta-analysis. 12 According to the results of the present study, CC patients, both responders and nonresponders, present a significantly higher number of reflux episodes with respect to NERD patients with typical symptoms. Indeed, in our series, the median number of reflux episodes is comparable to that previously reported in a group of 100 patients with CC 8 and this increased frequency of reflux episodes, irrespective of the acidity, may lead to an enhanced sensitivity to the gastric refluxate and, in particular, to a continuative vagal stimulation that is known to trigger cough bursts.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In our series, 88 of 156 patients reported an unsatisfactory response to PPIs, which is in agreement with findings of a recent meta-analysis. 12 According to the results of the present study, CC patients, both responders and nonresponders, present a significantly higher number of reflux episodes with respect to NERD patients with typical symptoms. Indeed, in our series, the median number of reflux episodes is comparable to that previously reported in a group of 100 patients with CC 8 and this increased frequency of reflux episodes, irrespective of the acidity, may lead to an enhanced sensitivity to the gastric refluxate and, in particular, to a continuative vagal stimulation that is known to trigger cough bursts.…”
Section: Discussionsupporting
confidence: 55%
“…A recent meta-analysis of nine clinical trials focusing on cough response to acid-suppressive therapy reported that only in two studies had PPIs significantly improved coughing with respect to placebo, and the benefit was substantial only in those patients presenting with pathologic oesophageal acid exposure. 12 On the other hand, Ours et al…”
Section: Introductionmentioning
confidence: 98%
“…More recently, two randomised controlled trials confirmed little or no effect of PPIs on chronic cough when compared with placebo (placebo, as is common in the trials of cough, having quite a marked effect over baseline) [55,56]. The authors of these trial reports [55,56] concluded that, given the evidence that PPIs may increase the likelihood of aspiration pneumonia [57], PPIs should not be routinely used in the treatment of a reflux cough, but should be reserved for patients exhibiting features of acid-related disease [58] or bronchospasm [59] in addition to cough. The place of pro-motility agents as an alternative to PPIs in the treatment of reflux cough remains controversial.…”
Section: Cough and Refluxmentioning
confidence: 99%
“…Uygun doz ve uygun süreli rejimlere yanıt veren bir alt grup hasta bulunmasına karşın halen bu alt grubu tanımlayabilecek ölçüde PPI çalış-maları yapılmamıştır. Kronik öksürükte 24 saatlik özofageal asit maruziyetinin pH monitorizasyonuyla objektif olarak değerlendirme yapılarak asit inhibitör tedavi yanıtının incelendiği bir sistematik derleme yazısına göre kanıtlanmış patolojik asit reflüsü olanlarda (%12.5-35.8 aralığında) terapotik kazanç, olmayanlara (%0.0-8.6 aralığında) göre daha fazla saptanmıştır [56].…”
Section: Kroni̇k öKsürükle İli̇şki̇li̇ Gastroözofageal Reflü Hastaliğininunclassified